Social cohesion and intercultural studies in the educational community - Марина Дєліні; Агостіно Портера; Марья Нестерова; Марта Мілані (Cхід, 2022)
The article shows the important role of social cohesion as a social phenomenon, its impact on the development of society and intercultural communication. The social role of trust, in particular, in the development of social cohesion, is also shown. Social cohesion acquires acute relevance and importance in the current time of social transformations, as cohesion allows communities overcome various fluctuations and changes. The social cohesion as complex social phenomenon has been analyzed in the focus of intercultural studies. The aim of the research was to investigate the important spheres of social cohesion related to intercultural communication in the educational community, in particular, in the university community of National Pedagogical Dragomanov University. The research conducted several times, including the crisis states of society – pan-demic and war conflict in Ukraine. This research continues social cohesion studies, which are conducted in the National Pedagogical Dragomanov University since 2016, and demonstrates one of the current stages. The methodological tool is an adaptation of the "Social Cohesion Radar" model at the university community level. The study is based on primary data from the author's questionnaire. The important role of social cohesion, trust and values in intercultural communication is demonstrated.